1986
DOI: 10.1090/s0273-0979-1986-15474-1
|View full text |Cite
|
Sign up to set email alerts
|

The cyclic homology and 𝐾-theory of curves

Abstract: ABSTRACT. It is now possible to calculate the K"-theory of a large class of singular curves over fields of characteristic zero. Roughly speaking, the ÜT-theory of a curve is the X-theory of its (smooth) normalization plus a few shifted copies of the if-theory of the field plus a "nil part." The nil part is a vector space depending only on the analytic type of the singularities, and may be computed locally. We completely compute the nil part for seminormal curves and give a conjectural calculation in general wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 8 publications
1
20
0
Order By: Relevance
“…We finally mention that for k a field of characteristic zero, the cyclic homology groups of A were calculated by Geller, Reid, and Weibel [12,Theorem 9.2] and that, in view of the affirmation by Cortiñas [4] of the KABI-conjecture made in [12], this gives a complete calculation of the groups K q (A, a).…”
Section: K(a) K(a)mentioning
confidence: 94%
“…We finally mention that for k a field of characteristic zero, the cyclic homology groups of A were calculated by Geller, Reid, and Weibel [12,Theorem 9.2] and that, in view of the affirmation by Cortiñas [4] of the KABI-conjecture made in [12], this gives a complete calculation of the groups K q (A, a).…”
Section: K(a) K(a)mentioning
confidence: 94%
“…In a series of papers ( [11], [8], [10], [9]) Geller, Reid and Weibel explored the idea that cyclic homology should be a precise measure for the failure of excision in the algebraic K-theory of Q-algebras, and did some conjectural calculations. The problem remained open (although it IS an exercise in [13]), until Cortiñas released a preprint [3] claiming the conjecture using Suslin and Wodzicki's results on nonunital rings [18].…”
Section: Introductionmentioning
confidence: 99%
“…[11]. In [10] the statement of Corollary 0.2 was conjectured to hold when A and B are commutative unital Q-algebras and B is a finite integral extension of A, (KABI conjecture) and it was shown its validity permits computation of the K-theory of singular curves in terms of their cyclic homology and of the K-theory of nonsingular curves. In [12] 0.2 was conjectured for unital Q-algebras and it was shown that for * = 2 the left hand side maps surjectively onto the right hand side.…”
Section: Introductionmentioning
confidence: 99%
“…An application of 0.3 to the computation of the K-theory of particular rings -other than coordinate rings of curves-in terms of their cyclic homology was given in [13,Thm. 3.1]; see also [10,Thm. 7.3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation